Chronic generalized fibrotic skin lesions from disseminated leishmaniasis caused by Leishmania martiniquensis in two patients from northern Thailand infected with HIV - S. Chiewchanvit (2018)
© 2015 The Authors. British Journal of Dermatology published by John Wiley & Sons Ltd on behalf of British Association of Dermatologists. Background Leishmaniasis is a newly emerging infection in Thailand. Most of the previous human cases have presented with the clinical features of visceral leishmaniasis and were mainly found in southern Thailand. Here we report the first two patients from northern Thailand presenting with disseminated cutaneous leishmaniasis. Objectives To determine the nature of the infection of leishmaniasis and to identify the species of parasite responsible. Methods Clinical investigations included the taking of biopsy samples and histology. Parasitological diagnosis was performed by establishment of Leishmania promastigote cultures, and identification was performed by DNA sequencing of four independent gene loci (ribosomal RNA internal transcribed spacer 1; large subunit of RNA polymerase II; heat shock protein 70; RPL23a intergenic sequence). Results Both patients were infected with HIV, and had multiple cutaneous lesions and accompanying visceral leishmaniasis. They had similar cutaneous manifestations characterized by chronic generalized fibrotic lesions, which were more prominent on traumatic areas. In both patients the parasite was identified as Leishmania martiniquensis. This is a recently described species that is distinct and only distantly related to the classical agents of cutaneous leishmaniasis in Asia (Leishmania major and Leishmania tropica) or of visceral leishmaniasis (Leishmania donovani and Leishmania infantum). Each patient responded well to therapy with intravenous amphotericin B followed by oral itraconazole. Conclusions Leishmania martiniquensis is a cause of cutaneous leishmaniasis in Thailand. What's already known about this topic? Leishmaniasis is an emerging disease in Thailand, presenting as cutaneous or visceral leishmaniasis, sometimes with accompanying HIV infection. Most of the reported infections have been attributed to so-called 'Leishmania siamensis', but this identification has been called into question. What does this study add? Here we demonstrate that cutaneous leishmaniasis in two patients from northern Thailand is caused by Leishmania martiniquensis. Retrospective analysis indicates that the majority of cutaneous leishmaniasis in Thailand is caused by L. martiniquensis.